Characterization of pineapple leaf fibers from selected Malaysian cultivars - Abd. Rahman, Mohamed; Mohd Salit, Sapuan; Mridha, Shahjahan; Abdan, Khalina (WFL Publisher, 2009)
Natural fibers can replace glass fibers in fiber-reinforced plastics. Pineapple leave fibers (PALF) have high cellulose contents and are mechanically sound as reinforcement in polymer composites. In Malaysia the focus of the pineapple industry is the fruits leaving the leaves mainly composted or burned thus wasting good potential source of fibers. PALF from three popular cultivars (Josapine, Sarawak and Moris Gajah) were characterized physically and mechanically in order to identify the best cultivar for producing fibers. The three cultivars had leaves with very similar cross-sections. Extracting PALF from fresh leaves was easy due to low fiber-tissue interfacial strength giving cleaner and intact fiber bundles and technical fibers. ‘Josapine’ fiber bundles were finest and varied least in their diameter followed by those of ‘Sarawak’ and ‘Moris’. Tensile strengths and Young’s moduli of the PALF from the three cultivars were higher than some reported values while elongations at break were lower. ‘Josapine’ PALF had the highest average tensile strength and Young’s modulus and the highest elongation at break. For PALF from the three cultivars, tensile strengths and moduli decreased with increasing diameter while elongation at break was not affected. PALF from Sarawak cultivar had the highest thermal stability followed by those from Josapine and Moris cultivars. Based on potential fiber quantity, fineness, mechanical properties and thermal stability, PALF from Josapine cultivar was best followed by those from Sarawak and Moris cultivars. Appropriate fiber extraction technique is required to produce good quality PALF in a reasonable quantity to make utilization of these excellent lignocellulosic fibers feasible.